IMPLEMENTASI CAMP CHARACTER BERBASIS PERMAINAN TRADISIONAL DALAM PEMBENTUKAN KARAKTER ANAK KELAS B DI TK ALLIM - Azizun Rahmawati; Pristie Kartika Amandari; Zulfa Shofiana; Winnuly (LPPM IAD Probolinggo, 2026)
This study aims to describe the Effectiveness of traditional game-based Camp Character and the character development of Grade B children at TK ALLIM Babat. Early character cultivation is crucial, supported by the potential of local wisdom through traditional games as an effective and contextual medium. Using a case study qualitative approach, this research involved Grade B children as subjects, and teachers, facilitators, and the head of school as key informants. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using Miles & Huberman's interactive data analysis model. The results show that the Camp Character at TK ALLIM Babat was implemented holistically and structured. A series of activities such as ceremonies, gymnastics, four traditional game posts (engklek, rope skipping, cublak-cublak suweng, egrang batok), horseback riding, Dhuhur prayer, and Al-Qur'an recitation proved. The effectiveness of the Camp Character activities in this study was observed through changes in children's behavior during the implementation of the program. These changes included improvements in cooperation, independence, discipline, responsibility, and sportsmanship, based on direct observational findings. Traditional games successfully created a fun and meaningful learning environment for early childhood in internalizing character values.